Screen-Printed Graphite Electrodes as Low-Cost Devices for Oxygen Gas Detection in Room-Temperature Ionic Liquids. - Lee, J.; Hussain, G.; Banks, C.; Silvester, Debbie (MDPI Publishing, 2017)
Screen-printed graphite electrodes (SPGEs) have been used for the first time as platforms to detect oxygen gas in room-temperature ionic liquids (RTILs). Up until now, carbon-based SPEs have shown inferior behaviour compared to platinum and gold SPEs for gas sensing with RTIL solvents. The electrochemical reduction of oxygen (O2) in a range of RTILs has therefore been explored on home-made SPGEs, and is compared to the behaviour on commercially-available carbon SPEs (C-SPEs). Six common RTILs are initially employed for O2 detection using cyclic voltammetry (CV), and two RTILs ([C2mim][NTf2] and [C4mim][PF6]) chosen for further detailed analytical studies. Long-term chronoamperometry (LTCA) was also performed to test the ability of the sensor surface for real-time gas monitoring. Both CV and LTCA gave linear calibration graphs-for CV in the 10-100% vol. range, and for LTCA in the 0.1-20% vol. range-on the SPGE. The responses on the SPGE were far superior to the commercial C-SPEs; more instability in the electrochemical responses were observed on the C-SPEs, together with some breaking-up or dissolution of the electrode surface materials. This study highlights that not all screen-printed ink formulations are compatible with RTIL solvents for longer-term electrochemical experiments, and that the choice of RTIL is also important. Overall, the low-cost SPGEs appear to be promising platforms for the detection of O2, particularly in [C4mim][PF6].